Peran Guru Tahfidz dalam Memotivasi Untuk Menghafal Al-Qur’an Siswa MI Al-Fatah Parakancanggah Banjarnegara - Fita Istikarini; Mukromin Mukromin; Chairani Astina (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The aims of this research are: (1) To determine the implementation of the tahfidz learning method at MI Al-Fatah Parakancanggah Banjarnegara, (2) To determine the role of tahfidz teachers in motivating students to memorize the Al-Qur'an at MI Al-Fatah Parakancanggah Banjarnegara, (3 ) To determine the supporting factors and inhibiting factors of the role of tahfidz teachers in motivating students to memorize the Al-Qur'an at MI Al-Fatah Parakancanggah Banjarnegara.The research carried out in this research is field research with a qualitative type of research: namely research that produces descriptive data rather than numerical data. The data methods used are observation, interviews and documentation. After the data is collected, it is then analyzed using qualitative descriptive analysis, namely data collection, data reduction, data presentation, and data conclusion.The research results show that the role of tahfidz teachers is very important in motivating students to memorize the Al-Qur'an at MI Al-Fatah Parakancanggah Banjarnegara. With motivation from the teacher, students can memorize the Al-Qur'an enthusiastically and well, so that they can make a large contribution to their memorization and the target of memorizing the Al-Qur'an can be achieved.